In the Process of Social Relations Characteristics, Methods and Development Mechanisms of Rational and Irrational Thinking - Tashniyazov Umirbek Khurramovich (Genius Journals, 2022)
This article presents a theoretical analysis of the characteristics, methods and mechanisms of development of rational and irrational thinking in the process of social relations, as well as analysis of problems, synthesis of details, and comparison of facts in rational thinking
Keywords: Social relations; rational thinking; irrational thinking; thinking mechanisms